2018
DOI: 10.1002/dmrr.3057
|View full text |Cite
|
Sign up to set email alerts
|

Serum cathelicidin as a marker for diabetic nephropathy in patients with type 1 diabetes

Abstract: Patients with T1DM and DN are characterized by increased serum cathelicidin level. There was an independent relationship between serum cathelicidin level and DN. Serum cathelicidin level can be used as an early marker for the presence and progression of DN in T1DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The antimicrobial peptide cathelicidin (CRAMP in mouse/rat, LL-37 in human) is expressed in many immune cells, such as epithelial cells, and genital cells 10 . CRAMP was initially reported as an immunomodulatory peptide that functions in many autoimmune diseases, such as psoriasis 11 , systemic lupus erythematous 12 , arthritis 13 , atherosclerosis 14 , and type 1 diabetes 15 . Recent studies have identified a role of CRAMP in cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial peptide cathelicidin (CRAMP in mouse/rat, LL-37 in human) is expressed in many immune cells, such as epithelial cells, and genital cells 10 . CRAMP was initially reported as an immunomodulatory peptide that functions in many autoimmune diseases, such as psoriasis 11 , systemic lupus erythematous 12 , arthritis 13 , atherosclerosis 14 , and type 1 diabetes 15 . Recent studies have identified a role of CRAMP in cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests a considerable short-term induction of CAMP expression and secretion by insulin, glucose, and/or incretins. Of note, CAMP has previously been reported to be linked to diabetes mellitus type 1 [ 25 ], and its circulating levels have been suggested as a marker for diabetic nephropathy [ 26 ]. While a recent study reported decreased CAMP serum concentrations in T2D patients [ 27 ], results from previously published studies are somewhat incongruent with this observation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%